Numerical Simulation and Experimental Study on Chip Radiator with Enhanced Heat Transfer Structure - Zhu Kai; Wang Huafeng; Wang Jianhui; Zhang Mi; Yang Yang (Zhileng xuebao)
The heat dissipation of super or large computer server CPU has become the bottleneck for the development of high performance computer, therefore the cooling of super or large computer server attracted more and more attention. This paper proposes a type of radiator for cooling of computer server chip, in which heat pipe which is embedded in the radiator base plate is assembled with fin as a whole. A test bench was built, and the performance of the plate type heat pipe radiator and the proposed radiator was compared experimentally. The temperature distribution of the heat pipe body, the fin and the uniform temperature board was simulated numerically. The heat transfer in the condensing section in the proposed radiator is enhanced, so the floor area of the proposed radiator is reduced 50% compared with the plate type heat pipe radiator, and the proposed radiator has a better temperature uniformity. Under the same conditions, the average temperature of the top radiator fin is only increased 17% when the heat flux is increased from 24.3 W/cm2 to 68.6 W/cm2.